Chemical composition of essential oils, biological and antioxidant activities of ferula orientalis growing in erzurum - Erman, Fazilet; Turkoglu, Semra (Parlar Scientific Publications, 2021)
Ferula orientalis (Apiaceae) is a plant that is used for medicinal purposes for hundreds of years thanks to the natural compounds it includes. This study aimed to determine the antimicrobial and antioxidant activities and volatile fat compounds in the edible parts of Ferula orientalis, which grows in certain regions in Turkey and is used as food. The volatile fat compounds of this species are investigated for the first time in this study. The surface parts of the plant material were extracted by using the Soxhlet device while using ethanol as the solvent agent. The ethanol contents of the extracts were removed in an evaporator, and the dry extracts (mg/mL) obtained were stored at +4 °C. The volatile fat compounds were determined by GC-MS, and the main compounds in these fats were determined as Quinic acid (43.83) and Sabinene (11.30). It was determined that the reducing power of Ferula orientalis, which was determined according to the Oyaizu method, was increased as the concentration increased. IC50 values for the DPPH free radical scavenging activity in 50, 100 and 250 ?L/mL concentrations were determined as 4.93, 181.50 and 299.65 ?g/mL, respectively. F. orientalis demonstrated the highest activity of metal chelating (51%) in the 250 ?L concentration. The results of the amount of total phenolic compound of the plant were determined as 51.115 ± 4.86 GAE / kg. Furthermore, it was determined that the plant did not demonstrate antimicrobial effects on the microorganism. These results indicated in the current study that plant extracts are a potential source of natural antioxidants. © by PSP
Keywords: Antimicrobial activities; Antioxidant activities; Essential oils; Ferula orientalis